Characteristics of Long-COVID care centers in Italy. A national survey of 124 clinical sites - Floridia, Marco; Grassi, Tiziana; Giuliano, Marina; Tiple, Dorina; Pricci, Flavia; Villa, Marika; Silenzi, Andrea; Onder, Graziano (Frontiers in Public Health, 2022)
Background: despite the growing clinical relevance of Long-COVID, there is minimal information available on the organizational response of health services to this condition. Methods: a national online survey of centers providing assistance for Long-COVID was implemented. Information collected included date of start of activity, target population, mode of assistance and of referral, type and number of specialists available, diagnostic and instrumental tests, use of telemedicine and of specific questionnaires. Results: between February and May 2022, 124 centers completed the survey. Half of them were situated in northern Italy. Most (88.9%) provided assistance through either outpatient visits or day hospital services. Eleven (8.9%) assisted paediatric patients. Access to centers included scheduled visits for previously hospitalized patients (67.7%), referral from primary care (62.1%), from other specialists (46.8%), and, less commonly, from other services. Almost half of the centers (46.3%) started their activity early in the pandemics (March-September 2020). Almost all (93.5%) communicated with primary care physicians, and 21.8% used telemedicine tools. The median number of patients followed was 20 per month (IQR 10-40). In most cases, the center coordinator was a specialist in respiratory diseases (30.6%), infectious diseases (28.2%), or internal medicine (25.0%). At least half of the centers had specialistic support in cardiology, respiratory diseases, radiology, infectious diseases, neurology and psychology, but roughly one quarter of centers had just only one (14.5%) or two (9.7%) specialists available. The clinical assessment was usually supported by a wide range of laboratory and instrumental diagnostics and by multidimensional evaluations. Conclusions: most of the centers had an articulate and multidisciplinary approach to diagnosis and care of Long-COVID. However, a minority of centers provided only single or dual specialistic support. These findings may be of help in defining common standards, interventions and guidelines that can reduce gaps and heterogeneity in assistance to patients with Long-COVID.